The Word That Redescribes the World : The Bible and Discipleship - Brueggemann, Walter (Book collections on Project MUSE., 2006)
"In the last several years, Walter Brueggemann's writings have directly addressed the situation of Christian communities in today's globalized context, with its consumerist lifestyles, vast inequalities, and near-imperial exercises of power. His insights, forged in rugged encounters with the texts of the Old Testament, are sharp, painful, and indispensable. In the People of Israel Brueggemann finds a model of an alternative community - anchored in YHWH, ever exploring new possibilities, and prophetically bent against empire."--